Framing Power in Japanâ€™s Digital Sphere: A Corpus-Based Functional Approach - Ketut Gede Adi Putra Laksana; Rohali Rohali; I Kadek Purnawan; Ni Di Ya (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2026)
The emergence of the term â€œJapanese Firstâ€ in public media discourse can be traced to the second quarter of 2025, based on documented reports and news coverage collected during the data compilation period. This study conducts a comparative analysis of political representations of the Japanese First issues by contrasting coverage in the English-language press and Indonesian-language press on online discourses. Drawing on a corpus-driven investigation of 45 news articles published in online discourses from July to September 2025, we disseminate how different news agencies represent, legitimise, and stigmatise the Japanese First issues.Â This study utilises a mixed method consisting of quantitative analysis to provide statistical analysis for linguistic features and qualitative analysis to describe the usage of its features, such as keywords, collocations, and KWIC, which are related to our study. The research combines a corpus-based approach with discourse analysis (CADA) to investigate language use in relation to transitivity analysis. The findings of our analysis reveal differences in transitivity patterns between two corpora in the news articles published in different languages. English-language discourse tends to emphasis perceptual and ideological framing that associates parties with specific values, beliefs, and moral imagery while the Indonesian-language discourse predominantly portrays the performative actions of parties.Keywords: Language and ideology, Japanese First, transivitas halliday, online discourseÂ ABSTRAKMunculnya istilah